Individual Case Studies of Japanese Knowledge Transfer via Training in Mexico’s Automotive Industry - Guzmán-Anaya, Leo (México y la Cuenca del Pacífico, 2022)
The automotive industry has been considered a source for achieving development in emerging economies. In an ideal setting, supplier firms and assembly plants work interconnected creating positive externalities, but it has been shown that this is difficult to achieve for developing countries. The case of Mexico stands out as a country that has successfully attracted major Japanese automotive assemblers but has struggled to include endogenous firms in the supply chains primarily due to the inability to meet technological and quality requirements. This study employs a qualitative case study methodology to analyze knowledge transfer processes to local firms that participated in a training project from the Japan International Cooperation Agency (JICA). The results show that through training, participating local firms improved quality and productivity measurements. The knowledge acquired was internalized and diffused within the firm allowing for industry-specific certifications, market growth, and market diversification.